Caracterização molecular de isolados de Trypanosoma cruzi obtidos de mulheres durante a fase crônica da doença de Chagas - Avelar, Juliana Boaventura (2008)
Chagas disease is a zoonotic disease caused by a protozoan plagued called Trypanosoma cruzi, it is a particular problem in Latin America, where it is estimated that 12 to 14 million people are infected. The populations of Trypanosoma cruzi can be divided into two major groups, the Trypanossoma cruzi I (TCI) and Trypanossoma cruzi II (TCII), the last being more heterogeneous and divided into five subgroups TCIIa, TCIIb, TCIIc, TCIId and TCIIe However, little is known of epidemiological and clinical implications of these ratings. The frequency of vertical transmission of Chagas disease can vary from 1.6 to 18.5% in accordance with the region and the methodology used in the studies. The aim of this study was to genetic characterization of 30 isolates of T. cruzi through the blood of patients with Chagas disease in the chronic phase, pregnant and not pregnant. The genetic characterization was performed with three different markers that amplified regions of the 18S and 24S α DNA ribosomal and mini-exon of the gene that allows classify the groups and subgroups of the parasite and the analysis of genetic variability among isolates of T. cruzi was performed the characterization of the variable region of minicicles of kDNA through the technique of Low-Stringency Single Specific Primer-PCR (LSSP-PCR). The 30 patients studied 75% (25/30) were women and 25% (5 / 30) not pregnant. The patients are the four different Brazilian regions being the States of Bahia 53.3% (16/30), Goiás 40.0% (12/30), Paraíba 3.3% (1 / 30) and the Federal District 3, 3% (1 / 30). The analysis of rDNA allowed show the TCII in 100% of the isolated populations in the regions studied, where the subgroup TCIIb/e has been detected in (96.66%) and TCIId in (3.33%) the latter is a sample of the group Control of the State of Bahia. The genetic variability between the 30 samples was 24.08 ± 14.4% share of bands among pairs. There was no difference between the share of bands patients of Bahia and Goiás, where the value of significance was less than 5%. There was no difference between the percentages of bands showed in analyses by age of the patients, gestational age and in the analysis of the groups of pregnant and not pregnant. In reviewing more than one tube of blood per patient coming evidenced profiles of signatures genomic complex and heterogeneous with 62.5% of bands shared less than 77% and only 37.5% had rates higher than 83% of bands sharing among samples. Suggesting so our isolates showed a great genetic variability.